Shared epitope defines distinct associations of cigarette smoking with levels of anticitrullinated protein antibody and rheumatoid factor - Ishikawa, Yuki; Ikari, Katsunori; Hashimoto, Motomu; Ohmura, Koichiro; Tanaka, Masao; Ito, Hiromu; Taniguchi, Atsuo; Yamanaka, Hisashi; Mimori, Tsuneyo; Terao, Chikashi (Annals of the rheumatic diseases, 2019)
ObjectsAlthough the association of cigarette smoking (CS) with susceptibility to rheumatoid arthritis (RA) has been established, the impact of CS on anticitrullinated cyclic peptide/protein antibody (ACPA) and rheumatoid factor (RF) levels in RA has yet been clear, especially in relation to shared epitope (SE) alleles.MethodsA total of 6239 subjects, the largest Asian study ever, from two independent Japanese cohorts were enrolled. Precise smoking histories, levels of ACPA and RF, and HLA-DRB1 allele status were withdrawn from databases. Associations between CS and high ACPA or RF levels, defined by the top quartiles, were evaluated. The effect of HLA-DRB1 alleles on the association was further investigated.ResultsCS at RA onset conferred the risks of high levels of both antibodies, especially RF (OR 2.06, p=7.4×10–14; ACPA, OR 1.29, p=0.012), suggesting that RF level is more sensitive to CS than ACPA level. The patients who had quitted CS before RA onset showed a trend of decreased risks of developing high levels of ACPA or RF, and the risks steadily decreased according to the cessation years. The association of CS with high ACPA level was observed only in subjects carrying SE alleles, while the association of high RF level was observed regardless of SE.ConclusionsCS confers the risks of high autoantibody levels in RA in different manners; CS interacts with SE alleles on ACPA level, while CS impacts on RF level despite SE allele. These data suggest novel distinct production mechanisms of RF and ACPA.